(untitled) (Biological Sciences - PJSIR, 1998)
Antiulcerogenic activities of aqueous extracts of two plant drugs were studied against normal pylorous ligated and aspirin ulcerated rats. Their effect on volume of gastric juice secreted, acid output, peptic activity, mucin activity and curative ratio were recorded. The percent incidence of ulcer, average number of ulcers per stomach and ulcer index were calcu- lated. Cichorium intybus showed a significant decrease in acid output and pepsin concentration in aspirin-ulcerated rats. A qualitative change in hexose and fucose concentration was found in pylorous ligated and aspirin-ulcerated rats. A 40% inhibition in ulcer .formation was recorded. A significant decrease in acid output was found in animals treated with aqueous extract of Phyllanthus emblica in normal pylorous ligated rats but statistically non significant change in acid output was recorded in aspirin-ulcerated rats. Both normal pylorous ligated and aspirin-ulcerated rats treated with aque- ous extracts of Phyllanthus emblicadid not show any antipeptic activity. However, a significant inhibition (54%) of ulcer formation was found.